The Distensibility of Reissner’s Membrane: A Comparative Analysis - Pender, Daniel J (Annals of Otology and Neurotology, 2022)
Background Distention of Reissner’s membrane in endolymphatic hydrops is a classical otopathologic finding in cases of Meniere’s disease. A recent double hit analysis raised the possibility that the variability in the distensile behavior in Reissner’s membrane may contribute to the vagaries of membrane pathology encountered in this disease. Such distensile variability is suspected to stem from the viscoelastoplastic behavior of the type IV collagen in Reissner’s basement membrane.Objective To analyze the known distensile characteristics of Reissner’s membrane for evidence of viscoelastoplastic behavior.Methods Extant data on human Reissner’s membrane were analyzed for distensile characteristics. These features were then compared to the known characteristics of viscoelastoplasticity as manifested by polymers in general as well as a variety of collagenous tissues. These tissues included a synthetic collagen membrane as well as selected mammalian tissues.Results The limited extant data on human Reissner’s membrane distensile behavior was found to manifest sigmoid load deformation at a lower strain rate of 0.47%/sec and a rigid rupture pattern at a 10-fold higher strain rate of 5.5%/sec. These characteristics were found to be similar to the general characteristics of polymer viscoelasticity, namely a sigmoid load deformation pattern at lower strain rate that stiffens and straightens as strain rate increases. Tensometric data from a synthetic collagen membrane and selected mammalian tissues were found to exhibit comparable load deformation patterns. These findings support the conclusion that human Reissner’s membrane behaves in a viscoelastoplastic manner.Conclusions Human Reissner’s membrane appears to exhibit viscoelastoplastic behavior comparable to that observed in other collagenous tissues. Such variable distensile behavior provides insight into why the degree of lesion distention before rupture in Meniere’s disease might vary depending on the dynamics of membrane loading and the resultant rate of membrane strain.
Keywords: balance diseases; hearing loss; inner ear conditions; Meniere's disease; otology